Effect of physical exercise on the motor skills acquisition among pupils with intellectual disability - Adedayo Adesokan (Indonesian Journal of Sport Management, 2022)
Decrease in physical activities among pupils with intellectual disability has been noted to affect motor skill acquisition, thus the need to carry out a study on possible ways to improve motor skill acquisition is necessary, this is the purpose of this study; which is to examine the effect of physical exercise on motor skills acquisition among pupils with intellectual disability. Three research hypotheses were posed in this work. A 2x2 pre-post test control group quasi-experimental research design was used for this study. The population was all students with intellectual disability in Kwara State as a sample of 40 children from schools located in Ilorin West Local Government Area of the state were selected through the use of simple random sampling technique. The instrument used for this study was a researcher’s designed rating scale. The rating scale had two section; section A contains the demographic information of the respondents such as gender, while section B contains 10 items which is a 3 likert scale, ranging from always, sometimes and never. The instrument was subjected to face and content validity by physical education teachers and experts in education. In order to determine the reliability of the instrument, the instrument was trial-test to 20 respondents who were not part of the sample size. Data collected were analyzed using frequency count, and percentage for the demographic information, while Analysis of Covariance (ANCOVA) was used for the research hypotheses. It is revealed that; physical exercise had significant effect on motor skills acquisition among pupils with intellectual disability, there was no significant effect of physical exercise on motor skills acquisition among pupils with intellectual disability based on gender and there was no significant interaction effect of physical exercise and gender on motor skills acquisition among pupils with intellectual disability. Thus, it can be concluded based on the findings of the study that, physical activities enhance motor skills acquisition among intellectually disabled pupils. Based on the findings, the study recommends among others that Sensitization of teachers should be regularly done in order to inform them of the importance of physical activities on learners with intellectual disabilty.